The Mediterranean Eating Pattern - Sheila Rahimpour; Karla P Shelnutt (EDIS)
Americans looking for an approach to healthy eating may want to consider the Mediterranean eating pattern. The Mediterranean eating pattern emphasizes fruits, vegetables, legumes, whole grains, nuts, and olive oil. It also includes moderate amounts of fish and poultry. This 3-page fact sheet discusses health benefits and ways to follow the Mediterranean eating pattern. Written by Sheila Rahimpour and Karla P. Shelnutt, and published by the UF/IFAS Department of Family, Youth and Community Sciences, May 2018. http://edis.ifas.ufl.edu/fy1476